Inhibition of Arenavirus Entry and Replication by the Cell-Intrinsic Restriction Factor ZMPSTE24 Is Enhanced by IFITM Antiviral Activity - Stott-Marshall, Robert J.; Foster, Toshana L. (Frontiers in Microbiology, 2022)
In the absence of effective vaccines and treatments, annual outbreaks of severe human haemorrhagic fever caused by arenaviruses, such as Lassa virus, continue to pose a significant human health threat. Understanding the balance of cellular factors that inhibit or promote arenavirus infection may have important implications for the development of effective antiviral strategies. Here, we identified the cell-intrinsic zinc transmembrane metalloprotease, ZMPSTE24, as a restriction factor against arenaviruses. Notably, CRISPR-Cas9-mediated knockout of ZMPSTE24 in human alveolar epithelial A549 cells increased arenavirus glycoprotein-mediated viral entry in pseudoparticle assays and live virus infection models. As a barrier to viral entry and replication, ZMPSTE24 may act as a downstream effector of interferon-induced transmembrane protein (IFITM) antiviral function; though through a yet poorly understood mechanism. Overexpression of IFITM1, IFITM2 and IFITM3 proteins did not restrict the entry of pseudoparticles carrying arenavirus envelope glycoproteins and live virus infection. Furthermore, gain-of-function studies revealed that IFITMs augment the antiviral activity of ZMPSTE24 against arenaviruses, suggesting a cooperative effect of viral restriction. We show that ZMPSTE24 and IFITMs affect the kinetics of cellular endocytosis, suggesting that perturbation of membrane structure and stability is likely the mechanism of ZMPSTE24-mediated restriction and cooperative ZMPSTE24-IFITM antiviral activity. Collectively, our findings define the role of ZMPSTE24 host restriction activity in the early stages of arenavirus infection. Moreover, we provide insight into the importance of cellular membrane integrity for productive fusion of arenaviruses and highlight a novel avenue for therapeutic development.